Development, stabilization, and characterization of nanoemulsion of vitamin D3-enriched canola oil - Khalid, Aafia; Arshad, Muhammad Umair; Imran, Ali; Haroon Khalid, Syed; Shah, Mohd Asif (Frontiers in Nutrition, 2023)
In this study, the oil-in-water nanoemulsion (NE) was prepared loaded with vitamin D3 into food-grade (edible) canola oil and stabilized by Tween 80 and Span 80 by using a water-titration technique having droplet sizes of 20 to 200 nm. A phase diagram was established for the influence of water, oil, and S-Mix concentration. The outcomes revealed that the particle size of blank canola oil nanoemulsion (NE) ranged from 60.12 to 62.27 (d.nm) and vitamin D3 NE ranged from 93.92 to 185.5 (d.nm), droplet size and polydispersity index (PDI)of both blank and vitamin D3 loaded NE results was less than 1, zeta potential results for blank and vitamin D3 loaded NE ranges from -9.71 to -15.32 mV and -7.29 to -13.56 mV respectively. Furthermore, pH and electrical conductivity of blank NE were 6.0 to 6.2 and 20 to 100 (µs/cm) and vitamin D3 loaded NE results were 6.0 to 6.2 and 30 to 100 (µs/cm), viscosity results of blank NE fall between 0.544 to 0.789 (mPa.s) and vitamin D3 loaded NE were 0.613 to 0.793 (mPa.s). In this study, the long-term stability (3 months) of canola oil NE containing vitamin D3 under room temperature (25 ͦ C) and high temperature (40 ͦ C) was observed.